Comparison of Kinetic Models for Boron Adsorption in Major Soil Groups of India - B.S. Dwivedi, S.P. Datta and Abir Dey, Niranjan Kumar, Mahesh C. Meena* (Journal of the Indian Society of Soil Science, 2021)
The aim of present study was to understand the boron (B) adsorption kinetics in soils. Three soils belonging to Alfisol, Vertisol and Inceptisol orders were selected. The soils were widely differed in their properties. Externally applied B content was allowed to equilibrate with intermittent shaking at different temperature levels (25 and 35 °C) for different intervals ranging from 0.5 to 72 h. Boron retention by soils followed decreasing order of: Vertisol > Inceptisol > Alfisol. Five different kinetic models viz. zero-order, first-order, parabolic, Elovich and power function were used for describing B adsorption kinetics in soils. The Elovich equation was proved to be the best among the various kinetic equations studied to describe B adsorption kinetics. The equilibrium concentration was achieved at 16 h at 35 °C whereas it takes more time at 25 °C. Adsorption of B decreased with a subsequent increase in temperature level.